First discovery of actinopterygian cutting-edged teeth from the middle Norian (Late Triassic) at the Tulong section, southern Tibet, China - Fang, Zichen; Cheng, Long; Jiang, Haishui; Wu, Xianlang; Lai, Xulong; Ogg, James G. (PeerJ, 2024)
Actinopterygians (ray-finned fishes) successfully passed through the Permian-Triassic Mass Extinction (PTME) and flourished in the Triassic with diverse feeding specializations and occupation of various trophic levels. Birgeria, one of the largest actinopterygian fish of the Triassic, was characterized by a strong, blunt rostrum and three rows of sharp cutting-edged teeth, making them the top predators in the Early Mesozoic oceanic ecosystem. These fishes rapidly radiated and diversified globally during the Early and Middle Triassic, but the fossil record is rare for the Neo-Tethys in the Late Triassic. Here, we report new actinopterygian teeth with cutting edges from Norian-age strata in the Tulong section, which was located on the northern margin of the Indian Plate at that time. The tooth features, such as the polished acrodin cap, the ratio of the acrodin cap in length, and the tiny vertical striae at the tooth base, suggest an affinity with Birgeria, which is reported in this region for the first time. Furthermore, we infer that the carnivorous Birgeria, which co-occurred with the enigmatic ichthyosaur Himalayasaurus tibetensis, played the role of predator in this part of the Neo-Tethys marine realm during the Late Triassic. These new findings increase the known diversity of actinopterygians during the Late Triassic and provide further insight into the marine fauna of this epoch.
Keywords: Actinopterygii; Birgeria; Himalayasaurus tibetensis; Qulonggongba formation; Tooth morphology